Uncivilized Men: Umwelt, Nature and Aesthetic Alienation in Werner Herzog’s The Enigma of Kasper Hauser and Aguirre, the Wrath of God - Wils, Tyson (Cinémas)

(untitled) (Cinémas, 2025)
Drawing on films such as The Enigma of Kasper Hauser and Aguirre, the Wrath of God, I examine the portrayal of nature in the films of German director Werner Herzog. I argue that the filmmaker aesthetically alienates nature and that this experience facilitates viewers perceiving the world through a different consciousness, creating an immersive experience that is outside of a narrative perspective. This can lead spectators to lose themselves in the film’s unfolding reality in an embodied state of diverse meanings and affects. I contextualize this experience of alienation in terms of the concept of Umwelt and the phenomenological realism of film theorist Siegfried Kracauer. In cinema, the Umwelt can relate to narrative structure and how the natural world can symbolize emotional aspects of the story while disrupting the linear narrative flow. Additionally, Umwelt can involve the use of optical techniques to create unfamiliar experiences of the world. I demonstrate not only how Herzog applies both these elements in his films, but also how these Umweltian images relate to Kracauer’s notion that film is able to redeem “physical reality.”